COMPETITIVE PRESSURES ON THE ARTISAN COFFEE ROASTER SEGMENT IN THE STATE OF MINAS GERAIS, BRAZIL: A MULTI-CASE STUDY - Guimarães, Elisa Reis; de Andrade, Helga Cristina Carvalho; Cozadi, Álvaro dos Reis; Antonialli, Luiz Marcelo; dos Santos, Antônio Carlos (Coffee Science - ISSN 1984-3909, 2018)
The specialty coffee market is still little known and underexplored in Brazil, motivating an analysis of the competitive pressures and structure of the artisan coffee roaster segment in the state of Minas Gerais, in order to better understand it and encourage the adoption of specific policies for its expansion, besides comparing it to the commodity coffee roasting segment. A multi-case study was performed with three companies in this segment through in-depth interviews with their owners. There were significant changes in the competitive forces that shape the coffee industry, when comparing the specialty and commodity coffee segments, both in intensity and in motivations. Among the suggested policies to support the specialty coffee segment are its promotion and dissemination through “consumer education” and awareness raising on the differentiated properties of these products, besides providing subsidized courses and specializations for those who wish to be involved in this marketplace.